2021
DOI: 10.1016/j.celrep.2021.109072
|View full text |Cite
|
Sign up to set email alerts
|

A collection of toolkit strains reveals distinct localization and dynamics of membrane-associated transcripts in epithelia

Abstract: Visualizing mRNA in real time in vivo at high resolution is critical for a full understanding of the spatiotemporal dynamics of gene regulation and function. Here, using a PP7/PCP-based mRNA-tagging approach, we construct a collection of tissue-specific and differentially expressed toolkit strains for visualizing mRNAs encoding apical, basolateral, and junctional proteins in Caenorhabditis elegans epithelia. We precisely delineate the spatiotemporal organization and dynamics of these transcripts across multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 65 publications
(61 reference statements)
2
11
0
Order By: Relevance
“…Complementarily to our findings in the early embryos, recent studies of later developmental stages identified 8 transcripts (dlg-1, ajm-1, sma-1, vab-10a, erm-1, pgp-1, magu-2, and let-413), including erm-1, that enrich to regions of the plasma membrane adjacent to apical junctions (Li et al, 2021;Tocchini et al, 2021). In particular, dlg-1 mRNA localizes through a translation-dependent pathway (Tocchini et al, 2021).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Complementarily to our findings in the early embryos, recent studies of later developmental stages identified 8 transcripts (dlg-1, ajm-1, sma-1, vab-10a, erm-1, pgp-1, magu-2, and let-413), including erm-1, that enrich to regions of the plasma membrane adjacent to apical junctions (Li et al, 2021;Tocchini et al, 2021). In particular, dlg-1 mRNA localizes through a translation-dependent pathway (Tocchini et al, 2021).…”
Section: Discussionsupporting
confidence: 84%
“…Future studies will determine the machinery required to traffic erm-1 , and transcripts like it. A recent study live-imaging erm-1 mRNA movements reported reduced erm-1 enrichment at the membrane upon knocking down a dynein motor (DHC-1), suggesting erm-1 localization could require this component of cytoskeletal trafficking (Li et al, 2021). It will also be interesting to determine whether erm-1 translation is paused or active during the trafficking process and whether multiple rounds of translation occur at the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Complementing our findings in the early embryos, studies of later developmental stages identified 8 transcripts (dlg-1, ajm-1, sma-1, vab-10a, erm-1, pgp-1, magu-2, and let-413), including erm-1, that enrich to regions of the plasma membrane adjacent to apical junctions (Li et al, 2021;Tocchini et al, 2021). In particular, dlg-1 mRNA localizes through a translation-Development • Accepted manuscript dependent pathway (Tocchini et al, 2021).…”
Section: Discussionsupporting
confidence: 81%
“…Co-translational mechanisms for mRNA delivery have been described for mRNA encoding transmembrane and secreted proteins ( Nyathi et al, 2013 ). Recent studies have suggested that co-translational mRNA localization can also exist for transcripts encoding proteins in other subcellular locations ( Chouaib et al, 2020 ; Li et al, 2021 ; Hirashima et al, 2018 ; Safieddine et al, 2021 ; Sepulveda et al, 2018 ). To determine whether dlg-1 mRNA localization occurs co-translationally, we designed a transgene (tg) to interfere with normal translation by deleting two nucleotides (TG) within the start codon of an otherwise wild-type sequence that contained both exons and introns ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Localized mRNA in C. elegans has been observed for maternally provided mRNAs in early embryos ( Parker et al, 2020 ) and for RNAs in synapses of adult neurons ( Yan et al, 2009 ). Very recently, a new study addressed membrane-associated localization of mRNA through a PP7/PCP-tagging approach in later embryonic stages and found five mRNA ( erm-1 , pgp-1 , magu-2 , let-413 and ajm-1 ) to be enriched at these loci ( Li et al, 2021 ). Previous studies of Drosophila embryogenesis have shown that many mRNAs are localized subcellularly, including mRNAs coding for cytoskeletal and junctional components ( Jambor et al, 2015 ; Lecuyer et al, 2007 ; Ryder and Lerit, 2018 ).…”
Section: Discussionmentioning
confidence: 99%